2007
DOI: 10.1017/s0007114507332546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dehydroepiandrosterone on protein and fat digestibility, body protein and muscular composition in high-fat-diet-fed old rats

Abstract: The main objective of the present study was to examine the effects of dehydroepiandrosterone (DHEA) on the digestive efficiency of dietary protein and fat. Second, we analysed the specific changes in muscle composition induced by the hormone. DHEA was given in the diet (0·5 %, w/w) to 75-week-old, high-fat-fed Sprague -Dawley rats (n 11) for 13 weeks; age-and weight-matched rats fed on the same diet without DHEA supplementation were used as controls (n 10). To determine dietary protein and fat apparent digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…We had previously reported that DHEA administration to our rats led to significant reductions in food intake, body weight, total body fat content, the weight of different adipose depots, and adipocyte size (de Heredia et al 2007). In addition, we found that DHEA-treated rats had significantly lower serum insulin concentrations and a tendency to lower HOMA-IR index (Sánchez et al 2008).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We had previously reported that DHEA administration to our rats led to significant reductions in food intake, body weight, total body fat content, the weight of different adipose depots, and adipocyte size (de Heredia et al 2007). In addition, we found that DHEA-treated rats had significantly lower serum insulin concentrations and a tendency to lower HOMA-IR index (Sánchez et al 2008).…”
Section: Discussionmentioning
confidence: 67%
“…Besides, low serum concentrations of these hormones, they have been associated with certain pathological states that increase their prevalence during ageing. Among the beneficial effects of DHEA, we can find cancer prevention (Ratko et al 1991, Kawai et al 1995, amelioration of cognitive function (Yanase et al 1996), or protection against cardiovascular disease (Ebeling & Koivisto 1994), atherosclerosis (Nestler et al 1992), or obesity (Richards et al 2000, Abadie et al 2001, de Heredia et al 2007. Improvement of peripheral insulin sensitivity has also emerged as one of DHEA's relevant actions; indeed, we and other authors have previously observed that DHEA administration to rodents reduced significantly serum insulin concentrations (Richards et al 2000, Abadie et al 2001, Sánchez et al 2008.…”
Section: Introductionmentioning
confidence: 86%
“…At the age of 7 weeks rats were fed with a HF diet. The diet contained (expressed as a percentage of dry mass) 18.4% protein, 50.4% carbohydrates (50% of which was sucrose) and 19.6% fat; the energy content was 1880 kJ/100 g, and fat amounted for 39% total dietary energy [29]. Palm oil was used as source of fat, and fatty acid composition of the diet was 53.6% saturated fatty acids, 36.3% monounsaturated fatty acids, 9.5% polyunsaturated fatty acids and 0.6% trans fatty acids.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…DHEA administration has long been associated with reduced weight gain in growing animals and with weight loss in mature animals [23][24][25][26][27][28]. DHEA may reduce weight gain by inhibiting food intake [23,29] or may cause a metabolic effect, as evidenced by less weight gain despite no change in food intake [25,30]. In addition, DHEA treatment has antidiabetic effects in some strains of mice [20] and reduces serum insulin levels in hyperinsulinemic, diet-induced or genetically obese rats [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in body weight gain may be related to the decrease in food intake (Weindruch et al, 1984), or related to the decrease the abdominal or body fats (Cleary and Zisk, 1986;Villareal and Holloszy, 2004;Ma et al, 2008). However, other studies reported that DHEA treatment causes a decrease in the body weight (Tagliaferro et al, 1986;Mohan et al, 1990;Yamada et al, 1991;Han et al, 1998;Ng et al, 1999;Richards et al, 2000;Kopplow et al, 2005;de Heredia et al, 2007;Caldwell et al, 2014;Chen et al, 2015), and other studies found no effect for DHEA on body weight (Lea-Currie et al, 1997 a, b;Aragno et al, 2004;Sander et al, 2006;Miyazaki et al, 2016). The cause for the observed difference in body weight could be attributted to different DHEA regimes (de Heredia, et al, 2007), or due to different routes of DHEA administration that might lead to differences in circulating DHEA levels and differences in body weight (Miyazaki et al, 2016).…”
Section: Discussionmentioning
confidence: 99%